Trypanosoma cruzi arginine kinase characterization and cloning. A novel energetic pathway in protozoan parasites - Pereira, Claudio Alejandro (2000)
This work contains the first description of a guanidino kinase in a flagellar unicellular parasite. The enzyme phosphorylates L-arginine and was characterized in preparations from Trypanosoma cruzi, the ethiological agent of Chagas' disease. The activity requires ATP and a divalent cation. Under Standard assay conditions (1 mM L-arginine), the presence of 5-fold higher concentrations of canavanine or histidine produced a greater than 50% enzyme inhibition. The base sequence of this enzyme revealed an open reading frame of 357 amino acids and a molecular weight of 40,201. The amino acid sequence shows all of the characteristic consensus blocks of the ATP:guanidino phosphotransferase family and a putative 'actinin-type' actin-binding domain. The highest amino acid identities of the T. cruzi sequence, about 70%, were with arginine kinases from Arthropoda. Southern and chromosome blots revealed that the kinase is encoded by a single-copy gene. Moreover, Northern blot analysis showed an mRNA subpopulation of about 2.0 kilobases, and Western blotting of T. cruzi-soluble polypeptides revealed a 40-kDa band. The finding in the parasite of a phosphagen and its biosynthetic pathway, which are totally different from those in mammalian host tissues, points out this arginine kinase as a possible chemotherapy target for Chagas' disease.